3D-printed monolithic biofilters based on a polylactic acid (PLA) – hydroxyapatite (HAp) composite for heavy metal removal from an aqueous medium. Issue 51 (1st October 2021) - Fijoł, Natalia; Abdelhamid, Hani Nasser; Pillai, Binsi; Hall, Stephen A.; Thomas, Nebu; Mathew, Aji P.
Abstract : Water purification filters based on polylactic acid functionalised with hydroxyapatite were prepared by solvent-assisted blending and thermally induced phase separation (TIPS), extruded into filaments and processed via three-dimensional (3D) printing. Abstract : High flux, monolithic water purification filters based on polylactic acid (PLA) functionalised with fish scale extracted hydroxyapatite (HAp) were prepared by solvent-assisted blending and thermally induced phase separation (TIPS), followed by twin-screw extrusion into filaments and processed via three-dimensional (3D) printing. The printed filters with consistent pore geometry and channel interconnectivity as well as homogenous distribution of HAp in the PLA matrix showed adsorption capabilities towards heavy metals i.e. cadmium (Cd) and lead (Pb) with maximum adsorption capacity of 112.1 mg gHAp −1 and 360.5 mg gHAp −1 for the metal salt of Pb and Cd, respectively. The adsorption was found to be driven by a combination of ion exchange, dissolution and precipitation on HAp and surface complexation.